Implementasi Strategi Pemasaran Melalui Pendekatan DOT di Taman Hutan Raya Ir. H. Djuanda - Deva Syauqi Khairunnisa; Ilma Aghnia Ali Syahida; Fadila Aulia; Taufiq Hidayat (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2023)
This research is based on the results of the researcher's observations and experience that the availability of tourism facilities and infrastructure in one of the tourist destinations in Bandung, namely Ir. Forest Park. H. Djuanda is quite good, the suitability of the equipment provided by the management is good enough to meet the needs of tourists visit. However, there are several things that are lacking. As well as providing factual data and analyzing the tourism marketing strategy of Taman Hutan Raya Ir. H Djuanda with the DOT (Destination, Origin, Time) approach introduced by the tourism ministry. The implementation of this marketing strategy, if implemented well, is believed to increase the number of tourist visits to Ir. Forest Park. H Juanda.